Osteopatia hipertrófica pulmonar-alterações clínicas e radiográficas em um paciente canino - Hermeto, Larissa Correa [UNESP]; Fernandes, Suelen Sâmera Pereira; Jardim, Paulo Henrique de Affonseca; Mattei, Douglas Rodrigo; Pelisari, Thais (My University, 2013)
Hypertrophic osteopathy is a rare disease which has been reported in dogs often associated with primary or metastatic pulmonary neoplastic processes. A ten-year-old female mongrel was admitted to the veterinary hospital in the city of Dourados-MS for presenting prostration, limited mobility, and edematous swelling of all the limbs. The radiographic examination revealed soft tissues swelling and lattice-shaped periosteal reaction in the radius, ulna, and metacarpals. A diffuse tumor mass in the pulmonary parenchyma was also detected. The final diagnosis was hypertrophic osteopathy associated with metastatic lung adenocarcinoma.
Hypertrophic pulmonary osteopathy-clinical and radiographic alterations in a canine patient
Keywords: Dog; Lung neoplasma; Periosteal reaction